2022
DOI: 10.1038/s41467-022-29507-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of prime editing via xrRNA motif-joined pegRNA

Abstract: The prime editors (PEs) have shown great promise for precise genome modification. However, their suboptimal efficiencies present a significant technical challenge. Here, by appending a viral exoribonuclease-resistant RNA motif (xrRNA) to the 3′-extended portion of pegRNAs for their increased resistance against degradation, we develop an upgraded PE platform (xrPE) with substantially enhanced editing efficiencies in multiple cell lines. A pan-target average enhancement of up to 3.1-, 4.5- and 2.5-fold in given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…3a, Table 1). In similar independent studies, other groups have added a Zikavirus exoribonuclease-resistant RNA motif (xr-pegRNA), a G-quadruplex (G-PE), or a stem-loop aptamer (sPE) to the pegRNA 3ʹ extension and have shown comparable improvements to prime editing in mammalian cell culture [74][75][76] (Fig. 3a, Table 1).…”
Section: Table 1 (Continued) | Prime Editor and Pegrna Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…3a, Table 1). In similar independent studies, other groups have added a Zikavirus exoribonuclease-resistant RNA motif (xr-pegRNA), a G-quadruplex (G-PE), or a stem-loop aptamer (sPE) to the pegRNA 3ʹ extension and have shown comparable improvements to prime editing in mammalian cell culture [74][75][76] (Fig. 3a, Table 1).…”
Section: Table 1 (Continued) | Prime Editor and Pegrna Architecturesmentioning
confidence: 99%
“…In their enhanced prime editing system (ePE), these extended pegRNAs are also fused to a nicking sgRNA and co-delivered with Csy4 nuclease, 70 , pegRNAs carrying the F + E crRNA scaffold 54,78 , and ePE pegRNAs 77 improve prime editor and pegRNA expression. epegRNAs 54 , ePE pegRNAs 77 , xr-pegRNAs 74 , G-PE pegRNAs 75 and sPE pegRNAs 76 reduce pegRNA degradation. PE2* 68 , PEmax 53 , CMP-PE-V1 63 and hyPE2 71 improve localization and/or DNA targeting of the prime editor complex.…”
Section: Table 1 (Continued) | Prime Editor and Pegrna Architecturesmentioning
confidence: 99%
“…However, PE-mediated correction of pathologic phenotype has been demonstrated ( Zhang H. et al, 2022a ; Zhang H. et al, 2022b ). Different strategies to improve PEs have been developed, either stabilizing the pegRNA ( Liu et al, 2021 ; Zhang G. et al, 2022 ), or manipulating repair pathways ( Chen et al, 2021 ; Ferreira da Silva et al, 2022 ), or a combination of both ( Chen et al, 2021 ; Jiang and Yao, 2022 ). Furthermore, by inserting specific same-sense mutations in the reverse transcription template of pegRNA or by altering the pegRNA secondary structure, efficiency could be significantly improved ( Li et al, 2022 ).…”
Section: Gene Editing Toolsmentioning
confidence: 99%
“…They also adopted the second strategy: introducing same-sense mutations at appropriate positions in the RT template portion of pegRNA (spegRNA), which increased the base-editing efficiency by an average of 353-fold. Zhang et al resisted pegRNA degradation by appending a viral exoribonuclease-resistant RNA motif (xrRNA) to the 3′ end extension of pegRNA, and the resulting xrPE had 3.1-, 2.5-, and 4.5-fold enhancements, respectively, for base conversions, small insertions, and small deletions in a variety of cell lines compared to PE3 [ 32 ]. Recent studies have also reported the modification of pegRNA with a human telomerase RNA (hTR) G-quadruplex (G 3 N 1-3 G 3 N 1-3 G 3 N 1-3 G 3 ) to improve the stability of pegRNA, resulting in G-PE with editing efficiency similar to that of the PE system using evopreQ1, while the G-quadruplex is shorter than evopreQ1 and xrRNA [ 33 ].…”
Section: Improvements In Prime Editorsmentioning
confidence: 99%